Komunikasi Pemasaran Melalui Instagram Dalam Menarik Minat Pembeli di Warkop Cek Ris Purwokerto : Studi Kasus pada Warkop Cek Ris Purwokerto - Fauziyah Rahma Safitri; Dina Darozatun Nuraeni; Wanda Purnamasari (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines how marketing communication strategies are implemented through Instagram by Warkop Cek Ris in Purwokerto and evaluates their effectiveness in attracting consumer interest. The research applies a descriptive qualitative approach, with data collected through observation, interviews, and documentation.The findings reveal that Warkop Cek Ris optimizes Instagram by delivering a variety of content, including menu promotions, entertainment posts, and brand identity development. Various features such as feed, stories, reels, and paid advertisements are utilized as part of the strategy. This approach is considered effective in expanding audience reach and enhancing brand awareness, particularly after the use of paid ads, which significantly increased viewership. Furthermore, active engagement with followers and collaborations with food bloggers also play an important role in strengthening consumer trust and encouraging purchase intention.However, the effectiveness is not yet fully optimal, as there are still challenges such as a limited number of followers and the lack of conversion from reach into actual visits. Therefore, improvements in content creativity, posting consistency, and the optimization of collaboration and digital promotion strategies are needed